(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article focuses on the development of Uzbek classical music art, its current state, and future prospects. It discusses the preservation of musical heritage and its adaptation to modern demands, the role of young creators and performers, as well as the integration of music with other forms of art. Particular attention is given to the connection between traditional music and new creative directions, its contemporary influence, and the role of national music in gaining recognition worldwide. The article highlights the unique features of Uzbek music and its prospects for further development.